VIRTUAL PRESENTING a guide to formats, production and authentic delivery. - Cohen, James, 1981-; Sorrentino, Michael, 1982- ([S.l.] : ROUTLEDGE, 2023)
Responding to the widespread and continued acceleration of virtual working practices in recent years, Virtual Presenting provides a clear guide to producing, presenting, and broadcasting in a remote context. Unlike traditional studio production where a presenter is surrounded by a crew and cameras, the virtual presenter is often isolated or connected to a remote crew. Virtual Presenting explains how to make an authentic connection across great spaces, linked only via the Internet. Topics covered include how to build a virtual setup; how to appear on camera; how to appear confident and comfortable; and how to optimize your presentation voice. The authors demonstrate how to tell effective stories across the entire new media landscape of webcasting, webinars, livestreams, and virtual events. Finally, success stories and case studies from teachers, students, and professionals are interwoven to show how these guidelines translate into best practices. Virtual Presenting will be a valuable resource for students of media production and remote broadcasting as well as professionals looking to become stronger communicators and visual presenters.
Keywords: LANGUAGE ARTS & DISCIPLINES / Journalism; Webcasting; Internet videos -- Production and direction